Communication Network System In SL-PTT Program Technology Development - Nurhayati (HUMANUS : Jurnal Sosiohumaniora Nusantara, 2024)
The communication network system in the SL PTT program application is a system that must be continuous with each other. The network contributes to the implementation of development. The purpose of this study is to discuss from the framework of the concept of how the SLPTT network system can run well. This research uses a literature study approach. The results showed that there was a guarantee of the continuity of a controlled program so that it could be seen the diversity of each nature of the subsystem in a unified system. A system contains components or elements, which are interconnected together to facilitate the flow of information, matter, and energy. Each object is a system. Keywords: Farmer, System, SLPTT